(E)‐2‐Cyano‐3‐(5′‐piperidin‐1‐yl‐2, 2′‐bithien‐5‐yl)acrylic Acid: A Fluorescent Probe for Detecting Prefibrillar Oligomers. Issue 18 (29th April 2013) - Bellia, Francesco; Bonaccorso, Carmela; Bellia, Francesco; Cataldo, Sebastiano; Fortuna, Cosimo G.; Musumarra, Giuseppe; Pignataro, Bruno; Rizzarelli, Enrico
Abstract: The synthesis of ( E )‐2‐cyano‐3‐(5′‐piperidin‐1‐yl‐2, 2′‐bithien‐5‐yl)acrylic acid, a novel amyloid aggregation fluorescent probe, is reported. This new probe is able to monitor soluble oligomeric aggregates after 24 h, at which time Thioflavin T emission, commonly used to monitor amyloid fibril formation, remains unchanged. Atomic force microscopy, native polyacrylamide gel electrophoresis, and dynamic light scattering confirm that the earlier stages of aggregation are prefibrillar oligomeric species not possessing the amyloid structure. This new molecular scaffold expands the toolbox of fluorescent probes for the identification of prefibrillar oligomers, which is needed in studies aimed at the early detection of the soluble toxic aggregates that characterize the so‐called protein misfolding diseases. Abstract : ( E )‐2‐Cyano‐3‐(5′‐piperidin‐1‐yl‐2, 2′‐bithien‐5‐yl)acrylic acid (p‐TTCNAc) can be conveniently used as a fluorescent probe to identify prefibrillar oligomers of hen egg white lysozyme not detected by Thioflavin‐T (ThT).